ALUR PENALARAN SISWA DALAM PHYSICS PROBLEM SOLVING DITINJAU DARI PERSPEKTIF EPISTEMIC GAMES: TIPE ANSWER-MAKING - Sabir, Sabir (JSTT, 2016)
The research aimed to construct and to describe students’ reasoning map in physics problem solving by applying AMEG perspective. The research instruments consisted of respondent selection test, reasoning test and interview protocol. Respondents were six students from a senior high school in Palu. Data were collected through thinking-aloud and interview. The activities were recorded by video camera. The data of interview were  used to support data analysis results of thinking-aloud. Data analysis of reasoning map used AMEG perspective where there is two methods that is Answer Justification(AJ) method and Reasoning Answer(RA). Based on the data analysis, it could be stated  that students’ reasoning map was influenced by their conceptual mastery and mathematic ability. Construction of students’ reasoning map in physics problem solving was influenced by memory and intuition. It is needed further research to study productivity of problem solving for the each reasoning plot.